Role of green energy technology on ecological footprint in China: Evidence from Beijing-Tianjin-Hebei region - Zhao, Huiqing; Li, Yuling; Hao, Feng; Ajaz, Tahseen (Frontiers in Environmental Science, 2022)
In order to investigate the impact of green energy technology on the environmental sustainability of China, take the Beijing-Tianjin-Hebei region as an example, this paper first calculates the per capita ecological footprint(ef), ecological carrying capacity(ec) and ecological deficit(ed) of the Beijing-Tianjin-Hebei region from 1990 to 2019 by using the ecological footprint(EF) model, and then uses an expanded STIRPAT model and Partial Least Squares(PLS) regression to explore the impact and importance of green energy technology on EF in the Beijing-Tianjin-Hebei region. It is found that the ec of Beijing, Tianjin and Hebei is much lower than that of the ef from 1990 to 2019. It is always in the state of ecological deficit, and the sustainable development is faced with severe challenges. Progress in green energy technology can significantly reduce the EF of Beijing, Tianjin and Hebei. The importance of each factor on the EF of Beijing, Tianjin and Hebei is different. The degree of dependence on foreign trade and urbanization rate are important influencing factors of Beijing’s EF. Urbanization rate, per capita GDP, population size, energy consumption per unit GDP and built-up area are the important influencing factors of EF in Tianjin and Hebei. Therefore, to reduce the EF of Beijing, Tianjin and Hebei, it is necessary to accelerate the progress of green energy technology, develop compact ecological city and change people’s consumption patterns.